Dose–response and Cardiopulmonary Side Effects of the Novel Neuromuscular-blocking Drug CW002 in Man. (December 2016) - Heerdt, Paul M.; Sunaga, Hiroshi; Owen, Joel S.; Murrell, Matthew T.; Malhotra, Jaideep K.; Godfrey, Deena; Steinkamp, Michelle; Savard, Peter; Savarese, John J.; Lien, Cynthia A.
Abstract : Background: CW002 is a benzylisoquinolinium nondepolarizing neuromuscular-blocking drug found to be inactivated by cysteine in preclinical studies. The current study represents a dose escalation clinical trial designed to describe CW002 potency, duration, cardiopulmonary side effects, and histamine release. Methods: Healthy subjects anesthetized with sevoflurane/nitrous oxide were divided into five groups (n = 6), each receiving a fixed CW002 dose (0.02, 0.04, 0.06, 0.08, or 0.10 mg/kg), and one group (n = 4) receiving 0.14 mg/kg. Blood pressure and heart rate were continuously recorded along with airway dynamic compliance. Neuromuscular blockade was assessed with mechanomyography at the adductor pollicis. Arterial blood was obtained before and after CW002 injection for analysis of plasma histamine concentration. Potency was estimated from a baseline sigmoid Emax model. Results: ED50 was found to be 0.036 mg/kg (95% CI, 0.020 to 0.053 mg/kg) and ED95 0.077 mg/kg (95% CI, 0.044 to 0.114 mg/kg). At 0.14 mg/kg (1.8 × ED95 ), 80% twitch depression occurred in 94 ± 18 s with complete block in 200 ± 87 s. Clinical recovery (25% of maximum twitch) occurred in 34 ± 3.4 min, with a 5 to 95% recovery interval of 35.0 ± 2.7 min. The time to a train-of-four ratio greater than 0.9 ranged from 59 to 86 min. CW002 did not elicit histamine release or significant (greater than 10%) changes in blood pressure, heart rate, or dynamic airway compliance. Conclusions: In healthy subjects receiving sevoflurane/nitrous oxide, CW002 at 1.8 × estimated ED95 produces a clinical duration less than 40 min, elicits no histamine release, and has minimal cardiopulmonary side effects. Abstract : CW002 is a relatively potent nondepolarizing neuromuscular-blocking agent with a duration of action less than 40 min at ~1.8× the ED95 . During the dose range studied, CW002 elicited no histamine release and had minimal cardiopulmonary effects.